Investigation of Combined Steel-Concrete Structures with Inter-Story Seismic Isolator in Near-Fault Field - Ali Asghar Mortazavi (Iranian Society of Structrual Engineering (ISSE), 2020)
Seismic isolation systems represent one of the most effective solutions to reduce near-fault damages; the systems can be used at either foundation or story levels. The main advantage of seismic isolation system is that it increases fundamental period of structure to longer periods. Among other advantages of seismic isolators, one can refer to the dissipation of input energy into the structure which lowers the transmitted acceleration to the above structure. In the present research, performance of combined concrete-steel structures with or without seismic isolation systems at story level, are investigated under near-field earthquakes. For this purpose, three structures of 4, 7, and 10 stories with/without seismic Lead Rubber Bearing (LRB) isolation systems with different damping ratios and periods were modelled. The analysis results indicate that, the isolation systems of longer period and smaller damping ratio were associated with lower relative displacement, acceleration and base shear, improving the structure performance. Results of analysis show that, with increasing the structure height (compare the results of the 10 story building with those of the 4 and 7 story counterparts), variations in base shear is reduced in the models with different isolation systems; i.e. the taller the structure, the more faded the role of the isolator. Furthermore, a study of the variations of damping ratio and period of isolator makes it obvious that, with increasing the period of isolators, shear force of the stories in the isolated structures decreases, while it slightly increases with increasing the damping percentage of the isolator.